Insight Into The Spin‐Vibronic Problem of a Mixed Valence Magnetic Molecular Cell for Quantum Cellular Automata. Issue 17 (20th July 2021) - Palii, Andrew; Korchagin, Denis; Aldoshin, Sergey; Clemente‐Juan, J. M.; Zilberg, Shmuel; Tsukerblat, Boris
Abstract: The effects of the vibronic coupling in quantum cellular automata (QCA) based on the square planar mixed valence (MV) molecular cells comprising four paramagnetic centers (spin cores) and two excess mobile electrons are analyzed in the important particular case when the Coulomb energy gap between the ground antipodal diagonal‐type two‐electron configurations and the excited side‐type configurations considerably exceeds both the one‐electron transfer parameter (strong U ‐limit) and the vibronic stabilization energy. Under such conditions the developed model involves the second‐order double exchange, the Heisenberg‐Dirac‐Van Vleck (HDVV) exchange and the vibronic coupling of the excess electrons with the molecular B 1 g ‐vibration composed of four full‐symmetric local vibrations. The latter interaction is shown to significant amplify the ability of the electric field produced by the driver‐cell to polarize the excess electrons in the working cell, which can be termed "the effect of the vibronic enhancement of the cell‐cell interaction". This effect leads to a redetermination of the conditions for switching between different spin‐states, as well as to a significant change in the shapes of the cell‐cell response functions. The obtained results demonstrate the importance of the vibronic coupling in all aspects (such as description of a free cell and cell‐cell response) of the theory of molecular QCA based on MV clusters. Abstract : Out for a spin? The vibronic coupling in quantum cellular automata based on the square planar mixed valence molecular cells comprising four paramagnetic centers and two mobile electrons is analyzed. The model involves the double exchange, the Heisenberg‐Dirac‐Van Vleck exchange and the vibronic coupling of the electrons with the breathing local modes. The latter interaction is shown to amplify the polarization of the working cell by the driver cell. This leads to a revision of the conditions for switching between different spin‐states, as well as to a significant change in the shape of the cell‐cell response function.